Research supporting service transformation: Family Drug and Alcohol Courts and understanding the factors that contribute to their success - Martin Doug (International Journal for Transformative Research)
Family Drug and Alcohol Courts (FDAC) were introduced to England in 2008 following their development in the USA. Pilots launched across the country adopted a family-based strategy with the aim to improve outcomes for children that live with parents who misuse substances or alcohol. The numbers of children entering the care system has increased with ‘subsequent new borns’ being a particular concern frequently becoming ‘looked after’ by the state at birth. This article will focus upon an initial phase of a study that tracked the establishment of an FDAC pilot. It reveals how the FDAC team collaborated with Judges and a diversity of professionals and parents to create conditions through which ground-breaking practice was forged. The environment created is unique as it is one fully set within the context of each family’s lived experience. Through this approach parents have become full participants in court proceedings as opposed to purely subject to them. As a result, significant numbers of children have remained with or been returned to their families.